Anneliese Landau's life in music : Nazi Germany to émigré California - Hirsch, Lily E., 1979- (Eastman studies in music, 2019)
A detailed and moving account of the life of Anneliese Landau, who, in Nazi Germany and later in émigré California, fought against prejudice to do notable work in music.